2012
DOI: 10.1016/j.cell.2012.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Long-Range Genomic Interactions at a Native Locus by Targeted Tethering of a Looping Factor

Abstract: Summary Chromatin loops juxtapose distal enhancers with active promoters but their molecular architecture and relationship with transcription remain unclear. In erythroid cells, the locus control region (LCR) and β-globin promoter form a chromatin loop that requires transcription factor GATA1 and the associated molecule Ldb1. We employed artificial zinc fingers (ZF) to tether Ldb1 to the β-globin promoter in GATA1 null erythroblasts in which the β-globin locus is relaxed and inactive. Remarkably, targeting Ldb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
601
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(617 citation statements)
references
References 49 publications
16
601
0
Order By: Relevance
“…Because LDB1 also has been reported to interact with other transcription factors, it is tempting to suggest a potentially general role for LDB1 in regulating cell typespecific, enhancer-dependent gene-expression programs. LDB1-mediated promoter:enhancer looping has been reported in the β-globin locus based on the homodimerization of LDB1 occupying both enhancer and promoter sites (22)(23)(24). Our data show that, in corticotropes, LDB1 can mediate looping to promoters without detectable promoter LDB1 binding.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Because LDB1 also has been reported to interact with other transcription factors, it is tempting to suggest a potentially general role for LDB1 in regulating cell typespecific, enhancer-dependent gene-expression programs. LDB1-mediated promoter:enhancer looping has been reported in the β-globin locus based on the homodimerization of LDB1 occupying both enhancer and promoter sites (22)(23)(24). Our data show that, in corticotropes, LDB1 can mediate looping to promoters without detectable promoter LDB1 binding.…”
Section: Discussionmentioning
confidence: 61%
“…LDB1 was postulated to play an important role in promoter:enhancer looping events and as a coactivator in several systems (21)(22)(23)(24)(33)(34)(35). To investigate its roles in gene transcription and in promoter:enhancer looping events in the POMC lineage, we performed GRO-seq after Ldb1 knockdown and observed that, of 3,378 genes down-regulated by siLdb1, 927 transcription units are located in direct proximity to the LDB1-occupied enhancers.…”
Section: Ldb1mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that risk-associated SNPs might abrogate chromatin looping and thus result in reduced promoter activity and subsequent transcription. 33 In addition, the risk SNPs reduced PRE1 activity on the CUPID1 promoter. However, in the absence of chromatin looping between PRE1 and the CUPID1 and CUPID2 promoter, the significance of this observation is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to binding sites containing GATA-E-box composite elements, like the +9.5 site, TAL1 occupies GATA motif-containing sites lacking a consensus E-box, presumably via recruitment by the GATA factor (28). The LIM domain binding-1 coregulator LDB1 promotes chromatin looping (39,40) and facilitates HSC maintenance, primitive hematopoietic progenitor generation, and erythroid differentiation (37,(41)(42)(43)(44). Certain patients with MonoMAC who lack GATA2 coding region mutations harbored deletion or point mutations in Fig.…”
Section: Significancementioning
confidence: 99%